Hubungan sarapan pagi dan status gizi dengan konsentrasi belajar pada siswa sekolah dasar - Arini Arini; Muammar Iksan; Hairunnisah Hairunnisah; Muhammad Noris (Holistik Jurnal Kesehatan, 2026)
Background: Concentration in learning is a crucial factor in the academic success of elementary school students. Concentration is influenced by various factors, including breakfast habits and nutritional status. Breakfast provides the brain with the energy it needs for cognitive function, while good nutritional status supports optimal brain growth and development. However, some students still have poor breakfast habits and nutritional problems that can affect their ability to concentrate. Purpose: To analyze the relationship between breakfast habits and nutritional status and concentration in students. Method: This quantitative, observational, and analytical study used a cross-sectional approach. The sample consisted of 84 students at Doro O'o Public Elementary School, Langgudu District, Bima Regency, West Nusa Tenggara Province, selected using a probability sampling technique using simple random sampling. Data on breakfast habits and concentration in learning were collected using a questionnaire, while nutritional status was measured using Body Mass Index for Age (BMI/Age). Data were analyzed using the Chi-Square test with a significance level of p < 0.05. Results: Most respondents had good breakfast habits (53.6%), good nutritional status (69.0%), and low levels of learning concentration (46.4%). Bivariate analysis showed a significant relationship between breakfast habits and learning concentration (p = 0.000). Furthermore, there was a significant relationship between nutritional status and learning concentration (p = 0.000). Conclusion: Breakfast habits and nutritional status are significantly related to learning concentration in elementary school students. Establishing healthy breakfast habits and maintaining optimal nutritional status are important to support cognitive function and improve students' learning concentration. Suggestion: Further research is recommended to develop studies using research designs that can explain causal relationships, such as cohort or experimental, so that the influence of breakfast and nutritional status on learning concentration can be understood more deeply.   Keywords: Breakfast; Learning Concentration; Nutritional Status.